2007
DOI: 10.1002/bip.20685
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the HIV‐1 protease dimer with interface peptides: Structural studies using NMR spectroscopy combined with [2‐13C]‐Trp selective labeling

Abstract: ABSTRACT:HIV-1 protease (HIV-1 PR), which is encoded by retroviruses, is required for the processing of gag and pol polyprotein precursors, hence it is essential for the production of infectious viral particles. In vitro inhibition of the enzyme results in the production of progeny virions that are immature and noninfectious, suggesting its This strategy has been explored by several groups who targeted the four-stranded antiparallel b-sheet that contributes close to 75% of the dimerization energy.Interface pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…One significant advantage of such a sensor design strategy is that other interfering proteases (i.e., false positives) could be differentiated from the target HIV-1 PR if they cleave the peptide substrate at different positions, thus improving the sensor accuracy and selectivity. Since the molecular size (with dimensions of 45 × 23 × 25 Å) (Frutos et al, 2007) of the HIV-1 PR (a 99 amino acid aspartyl protease that functions as a homodimer with only one active site) is larger than that of the protein pore transmembrane domain (20 Å diameter) (Wang et al, 2013), it cannot enter the nanopore and hence cannot produce current blockage events that might interfere with the identification of the target peptide(s) (Supporting Information, Figure S1). Our experimental results showed that, in the absence of the HIV-1 PR, the buffer solution containing the substrate peptide produced only one major type of current blockage with a mean residual current around −3.5 pA (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…One significant advantage of such a sensor design strategy is that other interfering proteases (i.e., false positives) could be differentiated from the target HIV-1 PR if they cleave the peptide substrate at different positions, thus improving the sensor accuracy and selectivity. Since the molecular size (with dimensions of 45 × 23 × 25 Å) (Frutos et al, 2007) of the HIV-1 PR (a 99 amino acid aspartyl protease that functions as a homodimer with only one active site) is larger than that of the protein pore transmembrane domain (20 Å diameter) (Wang et al, 2013), it cannot enter the nanopore and hence cannot produce current blockage events that might interfere with the identification of the target peptide(s) (Supporting Information, Figure S1). Our experimental results showed that, in the absence of the HIV-1 PR, the buffer solution containing the substrate peptide produced only one major type of current blockage with a mean residual current around −3.5 pA (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the inhibition of dimerization of HIV-1 protease subunits represents a unique target for potential intervention of HIV-1 replication. The strategy to target protease dimerization as a possible anti-HIV-1 modality has been explored (8,(11)(12)(13), and certain compounds have been reported as potential protease dimerization inhibitors. However, no direct evidence of dimerization inhibition by such compounds has been documented.…”
Section: Discussionmentioning
confidence: 99%
“…There are four anti-parallel ␤-sheets involving the N and C termini of both monomer subunits and they contribute close to 75% of the dimerization energy (10), explaining at least in part why DRV failed to dissociate mature protease dimer (see below). The termini interface has been explored as a dimerization inhibition target by several groups (11)(12)(13). We have also recently reported that certain peptides containing the dimer interface sequences amino acids 1-5 and amino acids 95-99 blocked HIV-1 infectivity and replication (14).…”
mentioning
confidence: 99%
“…Selected inhibitors may lead to the development of efficient peptidomimetics to inhibit virus attachment, entry, or replication. Examples of peptide-derived inhibitors, for which the inhibitory activity was confirmed, include an interface peptide acting as a dimerization inhibitor of the human immunodeficiency virus type 1 (HIV-1) protease (17) and enfuvirtide -HIV-1 entry inhibitor, a peptide derived from the viral envelope protein gp41 (43). As a result of the growing knowledge concerning the structure and functions of HCV proteins and the availability of the HCV replicon system (2, 32), a subset of antiviral agents comprising direct peptide-derived inhibitors of HCV enzymes such as protease and polymerase has been developed in recent years.…”
mentioning
confidence: 99%